The Relationship between Family Support and Anemia Prevention Efforts among Pregnant Women - Sukmawati Azahra; Susilawati Susilawati; Johan Budhiana (GLOBAL HEALTH SCIENCE GROUP, 2026)
Anemia in pregnant women remains a significant health issue and has the potential to cause various complications. The high prevalence of anemia among pregnant women indicates that prevention efforts still need to be improved, particularly through family support. The objective of this study was to determine the relationship between family support and anemia prevention efforts among pregnant women in the service area of the Baros Community Health Center in Sukabumi City. This study employed a correlational method with a cross-sectional approach. The population consisted of all pregnant women in the service area of the Baros Community Health Center in Sukabumi City, with a sample of 119 pregnant women selected using total sampling. The family support variable was measured using the PSS -Fa, with the validity test yielding a calculated r value > the table r value of 0.361, while the reliability test yielded a Cronbach’s Alpha value of 0.752. The anemia prevention efforts variable was based on the Guttman scale, with validity test results showing a p-value <0.05, indicating validity, except for items 9, 10, and 11, which were therefore excluded from the analysis; the reliability test yielded a Cronbach’s Alpha value of 0.373. Data were collected via questionnaires and analyzed using the Spearman rank test. Most respondents had strong family support, and most had effective anemia prevention measures in place; there was a significant association between family support and anemia prevention efforts among pregnant women (p = 0.000). There is a link between family support and efforts to prevent anemia in pregnant women. It is hoped that healthcare workers can enhance education and outreach regarding anemia prevention by involving families.